حزب الاستقلال المغربي وموقفه من الاحتلال الفرنسي وسياسته في الجزائر - مرجي عبدالحليم (University Of Eloued جامعة الوادي, 2023)
يعتبر حزب الاستقلال المغربي محركا فاعلا للساحة السياسية المغربية وممثلا للتيار العربي الإسلامي نظرا للمكانة السياسية والاجتماعية التي كان يتمتع بها، له قدرة على التعبئة الشعبية وصولا إلى التأثير في الساحة السياسية المغربية، والموقف السلطوي، الأمر الذي جعله الأقرب من المسألة الجزائرية وتوجهاتها، مما جعلها تحض باهتمامه من خلال تلك المواقف المختلفة تجاهها، فهذه الدراسة تهدف الى إبراز مدى اهتمامات الحزب بالمسالة الجزائرية، من خلال التنديد والتصدي للاحتلال الفرنسي وكل ممارساته التعسفية في حق الشعب الجزائري وشعوب المغرب العربي، وايضا فضح هذه الاساليب الاستعمارية المقيتة على جميع الاصعدة وخاصة الصعيد السياسي والاعلامي ومطالبة الاحتلال الفرنسي بالكف عن هذه الاساليب الوحشية والرحيل من منطقة المغرب العربي وتخلص المنطقة من رواسبه وتحقيق الشعب الجزائري لحريته واستقلاله. The Moroccan Independence Party is considered an effective engine of the Moroccan political arena and a representative of the Arab-Islamic trend due to the political and social position that it enjoyed. It had the ability to mobilize the people in order to influence the Moroccan political arena and the authoritarian position, which made it the closest to the Algerian issue and its orientations, which made it attract his attention through these different attitudes towards it. This study aims to highlight the extent of the party’s interests in the Algerian issue, by denouncing and confronting the French occupation and all its arbitrary practices against the Algerian people and the peoples of the Maghreb, and also exposing these abhorrent colonial methods at all levels, especially thepolitical and media levels, and demanding the French occupation to desist from these brutal methods and leave the Maghreb region and rid the region of its deposits and the Algerian people achieve their freedom and independence.
1962-1956م
Keywords: حزب الاستقلال; السياسة الاستعمارية; المسألة الجزائرية; الاستعمار; علال الفاسي; Independence party; colonial policy; the Algerian issue; colonization; Allal El Fassi